How Can Digital Health Technologies Contribute to Sustainable Attainment of Universal Health Coverage in Africa? A Perspective - Olushayo, Olu; Muneene, Derrick; Bataringaya, Juliet Evelyn; Nahimana, Marie-Rosette; Ba, Housseynou; Karamagi, Humphrey Cyprian; Dovlo, Delanyo (Frontiers in public health, 2019)
Innovative strategies such as digital health are needed to ensure attainment of the ambitious universal health coverage in Africa. However, their successful deployment on a wider scale faces several challenges on the continent. This article reviews the key benefits and challenges associated with the application of digital health for universal health coverage and propose a conceptual framework for its wide scale deployment in Africa.
Keywords: Resilient health systems; Digital health; e-Health; Universal health coverage; Sustainable development goals